Randomized trial to compare efficacy of polyester mosquito net mesh with polypropylene mesh in inguinal hernia surgery in northwestern India - Sanchit Jain; Abhishek Agarwal; Lakshman Agarwal; Laxmi Narayan Meena; Sumita Jain; Mohit Jain (Archives of Clinical and Experimental Surgery, 2016)
Objectives: Lichtenstein repair using mesh prosthesis is one of the most common repairs for inguinal hernia. In our country, the price of mesh contributes to a major portion of the total cost of the procedure. The study was conducted to compare the incidence of postoperative complications of using low-cost polyester mosquito net mesh with that of commercially available polypropylene mesh for inguinal hernia surgery by Lichtenstein repair and taking into consideration the cost of the operation. Methods: The study was a prospective randomized double-blind single-centre (government medical college) study. The study was conducted at SMS Medical College and Hospital, Jaipur, India, on 170 patients with inguinal hernia (45 bilateral and 125 unilateral) undergoing inguinal hernia surgery. Patients were randomly assigned to receive either of the meshes, and study of postoperative complications was carried out with follow-up of up to 1 year. The average cost of the procedure was also calculated. Chi-square test and Student's t-test were applied for significance testing (p-value and #8804; 0.05, significant; p-value < 0.001, highly significant). Results: No significant difference in incidence of postoperative complications between the two groups was observed. However, the cost of the operative procedure using the polyester net mesh was significantly lower (p-value < 0.0001). Conclusions: The results of the short-term follow-up clearly demonstrate that the incidence of postoperative complications from using polyester net mesh is well comparable with that of commercial polypropylene mesh. Using polyester mesh significantly reduces the cost of surgery and therefore it has a role in resource-limited settings. [Arch Clin Exp Surg 2016; 5(4.000): 200-205]